Sustainable Lignin for Carbon Fibers: Principles, Techniques, and Applications 2019
DOI: 10.1007/978-3-030-18792-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Carbon Fibres: Properties, Applications and Economic Efficiency

Abstract: Please check the manuscript for details of any other licences that may have been applied and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. You may not engage in further distribution of the material for any profitmaking activities or any commercial gain. You may freely distribute both the url (http://uhra.herts.ac.uk/) and the content of this paper for research or private study, educational, or not-for-profit purposes without p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…It has been concluded that, considering current environmental constraints, lignin precursors show also cost savings over conventional PAN precursors. In particular, it has been estimated that lignin carbon fiber can save $260 per ton from CO 2 environmental impact compared to PAN fibers (Ismail & Akpan, 2019). On the other hand, even though the chemistry of lignin deserves to be further investigated, in terms of performance, the mechanical properties of lignin carbon fibers made with current experimental lab-scale protocols do not meet the requirements of the aerospace industry.…”
Section: Production and Properties Of Non-oil Carbon Fibersmentioning
confidence: 99%
“…It has been concluded that, considering current environmental constraints, lignin precursors show also cost savings over conventional PAN precursors. In particular, it has been estimated that lignin carbon fiber can save $260 per ton from CO 2 environmental impact compared to PAN fibers (Ismail & Akpan, 2019). On the other hand, even though the chemistry of lignin deserves to be further investigated, in terms of performance, the mechanical properties of lignin carbon fibers made with current experimental lab-scale protocols do not meet the requirements of the aerospace industry.…”
Section: Production and Properties Of Non-oil Carbon Fibersmentioning
confidence: 99%